Permeability evolution of slowly slipping faults in shale reservoirs - Wu, Wei (2018)
Slow slip on preexisting faults during hydraulic fracturing is a process that significantly influences shale gas production in extremely low permeability “shale” (unconventional) reservoirs. We experimentally examined the impacts of mineralogy, surface roughness, and effective stress on permeability evolution of slowly slipping faults in Eagle Ford shale samples. Our results show that fault permeability decreases with slip at higher effective stress but increases with slip at lower effective stress. The permeabilities of saw cut faults fully recover after cycling effective stress from 2.5 to 17.5 to 2.5 MPa and increase with slip at constant effective stress due to asperity damage and dilation associated with slip. However, the permeabilities of natural faults only partially recover after cycling effective stress returns to 2.5 MPa and decrease with slip due to produced gouge blocking fluid flow pathways. Our results suggest that slowly slipping faults have the potential to enhance reservoir stimulation in extremely low permeability reservoirs.